A portable system based on turn-on fluorescent probe for the detection of hydrazine in real environment. (February 2022) - Chen, Yu; Mo, Wanqi; Cheng, Zhiyong; Kong, Fanwei; Chen, Chunxia; Li, Xiaobai; Ma, Hongwei
Abstract: Hydrazine is famous for its application in rocket fuel and is also an important reagent in chemical synthesis, pharmacy and agriculture. However, its extensive use and leakage can cause serious water pollution and a threat to human health due to the extreme toxicity and explosibility. Therefore, the development of efficient methods for hydrazine pollutant detection is of great significance for its timely treatment. Reported here is a new turn-on type fluorescence probe ACFP with low fluorescence background based on intramolecular charge transfer (ICT) mechanism. The probe ACFP exhibits superior selectivity and sensitivity (LOD = 2.5 μM) for hydrazine either in deionized water, tap water or pond water. More importantly, the probe is successfully integrated into the TLC plate and portable device (LOD = 0.027 μM) for the real complex environmental sample sensing, which demonstrates its appealing potential in the real-time, on-site detection of hydrazine. Graphical abstract: Image 1 Highlights: A fluorescent material with strong intramolecular charge transfer (ICT) was used for hydrazine. The turn-on fluorescence probe can realize the detection of hydrazine with high selectivity. A portable system exhibited high sensitivity to hydrazine in a real environment.